Tafsir Kontekstual Dan Implikasinya Dalam Pendidikan - Thayyibi, Muhammad Ilham (An-Nahdlah: Jurnal Pendidikan Islam, 2022)
Abstract : The purpose of this research is to know contextual interpretation and learning in education . This study uses a library research method, namely research analyzing written literature in the form of books and scientific journals as the main source, Contextual interpretation, namely the method used to study the Koran not only from the text, but also from language, historical background , sociology, and amtropology in accordance with the life and developments prevailing in the Arab nation and various approaches through it. The paradigm of contextual interpretation is the thoughts of Fazul Rahman, Abdullah Saeed, and Sahiron Samsudin. The implication of the interpretation of the Koran in the realm of education is the relationship or linkage of contestual interpretations in the realm of education, one of which is contextual learning. Learners to understand social conditions and then contextualize knowledge with social conditions. If in the Qur'an using contextual interpretation, in the field of education when learning uses contextual learning.